2000
DOI: 10.1029/2000jb900037
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a recently abandoned shear margin adjacent to ice stream B2, Antarctica, from ice‐penetrating radar measurements

Abstract: Abstract. Satellite imagery of the area between ice streams B1 and B2, Antarctica, shows a lineation on the surface of the ice sheet of uncertain origin. Ice motion in the area (2 m yr-•) is 2 orders of magnitude slower than that of the surrounding streams and shows no significant variation that could explain the feature. A low-power, high-resolution radar system was used to image the upper 80 m of the ice sheet between the two ice streams; the survey shows that the lineation is associated with what is likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 66 publications
4
68
1
Order By: Relevance
“…There is no convincing evidence of their occurrence but Clarke et al (2000) identified several features described as entrained morainal debris at the base of a recently abandoned shear margin of Ice Stream B in West Antarctica. Further offshore in West Antarctica, there are also descriptions of 'laterally accreting ridges' marking the position of the lateral margins of palaeo-ice stream tracks (Shipp et al, 1999).…”
Section: Observations Of Lateral Shear Margin Morainesmentioning
confidence: 98%
“…There is no convincing evidence of their occurrence but Clarke et al (2000) identified several features described as entrained morainal debris at the base of a recently abandoned shear margin of Ice Stream B in West Antarctica. Further offshore in West Antarctica, there are also descriptions of 'laterally accreting ridges' marking the position of the lateral margins of palaeo-ice stream tracks (Shipp et al, 1999).…”
Section: Observations Of Lateral Shear Margin Morainesmentioning
confidence: 98%
“…This area is characterized by buried crevasses but also reveals several features at the base of the ice sheet, directly below the inferred former margin. The origin of these features is unknown, but Clarke et al (2000) speculate that some of them may represent 'entrained morainal debris'. This is largely based on the fact that a drilling experiment encountered abnormal resistance on reaching such a feature and that the drill tip showed signs of fresh scratches on arriving at the surface.…”
mentioning
confidence: 95%
“…Using ice-penetrating radar, Clarke et al (2000) have found a recently abandoned shear margin of Ice Stream B. This area is characterized by buried crevasses but also reveals several features at the base of the ice sheet, directly below the inferred former margin.…”
mentioning
confidence: 98%
“…Fast inward margin migration (as seen at G4) is best explained by the advection of colder ice from adjacent ridges into the ice stream and is not unprecedented (Van der Veen and Whillans, 1996;Jacobson and Raymond, 1998;Raymond and others, 2001). Clarke and Bentley (2000) estimated an inward migration rate of 100 m a -1 for the south margin of WIS (near G1n/G2n) as it migrated from the 'Fishhook' starting $200 years ago. Similarly, Jacobel and others (2000) suggested that the multiple scars on the north margin of Kamb Ice Stream indicate that the margin moved inward in rapid jumps.…”
Section: Margin Migrationmentioning
confidence: 99%